Phenolic Profile, Sugar Composition, and Antioxidant Capacities of Some Common Date Palm (Phoenix dactylifera L.) Cultivars as a Potential Nutraceutical and Functional Food Ingredients - Imen Bettaieb; Ahlem Kilani; Khadija Ben Othman; Mohamed Ali Benabderrahim; Walid Elfalleh (Journal of Food Quality)
Date palm (Phoenix dactylifera L.), a strategic oasian species in most Mediterranean regions, is often known by the commercialized Deglet Nour variety. However, many other common varieties that might have high importance are neglected. The current study aims to evaluate the nutraceutical and functional properties of six common date palm cultivars, collected from three Tunisian oasian regions. The biochemical composition and antioxidant potential of these date cultivars were investigated. Total polyphenols (TPP), total flavonoids (TF), and condensed tannins (CT) contents varied significantly between varieties. In particular, the Ftimi cultivar had the highest amounts of TPP, TF, and CT (204.04 ± 12.85 mg·GAE/100 g·FW, 117.35 ± 7.49 mg·RE/100 g·FW, and 147.93 ± 7.65 mg·CTE/100 g·FW, respectively). Similarly, this cultivar exhibited the highest antioxidant activity with 131.59 ± 11.54 mg·TE/100 g·FW and 106.57 ± 2.33 mg·TE/100 g·FW, respectively, for DPPH and ABTS+ assays. Contrary to the Deglet Nour variety, the six common dates contain a high amount of fructose and glucose (reducing sugars) and a low content of sucrose. LC-ESI-MS analysis showed that “Kenta” had the highest number of polyphenolic compounds (19 compounds) followed by “Ftimi” with 18 compounds, whereas “Deglet Nour” has only 15. Six major compounds (quinic acid, epicatechin, rutin, hyperoside, luteolin 7-O-glucoside, and kaempferol) were omnipresent. These findings highlight the high potential of neglected date palm varieties and confirm their richness with nutraceuticals and natural antioxidants.